Development of Sodium Dodecyl Sulfate Based Electrochemical Sensor for Tartrazine Determination - Raril,C. (2021)
Abstract Sodium dodecyl sulfate modified carbon paste electrode (SDSMCPE) was prepared as a sensor for Tartrazine (TR) detection, at 0.2 M PBS, with pH 6.5. TR Electrocatalytic activity was found to be significantly improved compared to those obtained using a conventional paste electrode. TR electrochemical oxidation was investigated by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). SDSMCPE showed TR electrocatalytic oxidation in the linear range from 2×10-5 to 5×10-5 M and from 6×10-5 to 1.1×10-4 M, with the detection limit of 52×10-7 M. The proposed SDSMCPE-sensor exhibited enhanced electrochemical sensing, selectivity and stability for TRdetection. Finally, the use of a SDSMCPE-sensor was demonstrated for TRdetection in a lemon yellow powder sample.